PAI‐1 5G/5G genotype is an independent risk of intracranial hemorrhage in post‐lysis stroke patients - Szegedi, István (Ann Clin Transl Neurol, 2019)
OBJECTIVE: Thrombolysis by recombinant tissue plasminogen activator (rt‐PA) is the main pharmacological therapy in acute ischemic stroke (IS); however, it is only effective in a subset of patients. Here we aimed to investigate the role of plasminogen activator inhibitor‐1 (PAI‐1), an effective inhibitor of t‐PA, and its major polymorphism (PAI‐1 4G/5G) in therapy outcome. METHODS: Study population included 131 consecutive IS patients who all underwent thrombolysis. Blood samples were taken on admission, 1 and 24 h after rt‐PA infusion. PAI‐1 activity and antigen levels were measured from all blood samples and the PAI‐1 4G/5G polymorphism was determined. Clinical data including NIHSS were registered on admission and day 1. ASPECTS was assessed using CT images taken before and 24 h after thrombolysis. Intracranial hemorrhage (ICH) was classified according to ECASS II. Long‐term outcome was defined 90 days post‐event by the modified Rankin Scale (mRS). RESULTS: PAI‐1 activity levels dropped transiently after thrombolysis, while PAI‐1 antigen levels remained unchanged. PAI‐1 4G/5G polymorphism had no effect on PAI‐1 levels and did not influence stroke severity. PAI‐1 activity/antigen levels as measured on admission were significantly elevated in patients with worse 24 h ASPECTS (<7). Logistic regression analysis including age, sex, NIHSS on admission, BMI, history of arterial hypertension, and hyperlipidemia conferred a significant, independent risk for developing ICH in the presence of 5G/5G genotype (OR:4.75, 95%CI:1.18–19.06). PAI‐1 levels and PAI‐1 4G/5G polymorphism had no influence on long‐term outcomes. INTERPRETATION: PAI‐1 5G/5G genotype is associated with a significant risk for developing ICH in post‐lysis stroke patients.